The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1021/acs.est.1c01483
|View full text |Cite
|
Sign up to set email alerts
|

Selective Capacitive Removal of Heavy Metal Ions from Wastewater over Lewis Base Sites of S-Doped Fe–N–C Cathodes via an Electro-Adsorption Process

Abstract: The pollution of toxic heavy metals is becoming an increasingly important issue in environmental remediation because these metals are harmful to the ecological environment and human health. Highly efficient selective removal of heavy metal ions is a huge challenge for wastewater purification. Here, highly efficient selective capacitive removal (SCR) of heavy metal ions from complex wastewater over Lewis base sites of S-doped Fe−N−C cathodes was originally performed via an electro-adsorption process. The SCR ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(33 citation statements)
references
References 55 publications
0
26
0
Order By: Relevance
“…Researchers are currently exploring various methods to address contaminant removal, including ion exchange, biochar, reverse osmosis, adsorption, and a selective capacitive removal technology employing electro-adsorption or capacitive deionization. 7,10,12,19,23,24 This work examined the adsorption method, using magnetite (Fe 3 O 4 ) particles as the adsorbent. Adsorption is efficient, simple, and produces less byproducts than methods such as membrane filtration, ion exchange, and chemical precipitation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers are currently exploring various methods to address contaminant removal, including ion exchange, biochar, reverse osmosis, adsorption, and a selective capacitive removal technology employing electro-adsorption or capacitive deionization. 7,10,12,19,23,24 This work examined the adsorption method, using magnetite (Fe 3 O 4 ) particles as the adsorbent. Adsorption is efficient, simple, and produces less byproducts than methods such as membrane filtration, ion exchange, and chemical precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…The release and improper care of contaminated wastewaters pose serious threats to the environment, aquatic life, and human health, and the need for an efficient and economical method for contaminant removal is apparent. Researchers are currently exploring various methods to address contaminant removal, including ion exchange, biochar, reverse osmosis, adsorption, and a selective capacitive removal technology employing electro-adsorption or capacitive deionization. ,,,,, This work examined the adsorption method, using magnetite (Fe 3 O 4 ) particles as the adsorbent. Adsorption is efficient, simple, and produces less byproducts than methods such as membrane filtration, ion exchange, and chemical precipitation. ,,, Fe 3 O 4 is inexpensive, already exists in the environment, and has several favorable characteristics including biocompatibility, magnetic susceptibility, and an easily modified surface. ,,,, Magnetic properties allow for easy and efficient collection, reducing chemicals needed for removal and decreasing the production of secondary pollutants. ,, Additionally, Fe 3 O 4 can effectively capture anions and cations across a range of pH values. ,,,, Further, Fe 3 O 4 has demonstrated potential in applications such as magnetic inks, MRI contrast agents, and water treatment. …”
Section: Introductionmentioning
confidence: 99%
“…17 On the other hand, surface functional groups such as -OH and -COOH always serve as anchoring sites for metal ions via electrostatic attraction or coordination, playing a critical role in heavy metal removal. [18][19][20][21] Zhang et al reported a titanium peroxide-based adsorbent for the removal of Tl + via the formation of an inner-surface complex with hydroxyl groups. 22 To date, cation exchange and surface functional group-assisted coordination are the most mainstream adsorption mechanisms for Tl + removal from water.…”
Section: Introductionmentioning
confidence: 99%
“…These dissolved heavy metal ions in water can cause adverse effects on aquatic ecosystems. Long−term exposure to water which has been contaminated by heavy metals can cause serious harm to human health [3][4][5][6]. Lead ion (Pb 2+ ) is a common pollutant in industrial wastewater, which can cause human dysfunction or serious lesions if ingested in large quantities or for a long time [7,8].…”
Section: Introductionmentioning
confidence: 99%